AKUAPONIK DALAM MENUNJANG PROGRAM B2SA DI YAYASAN AL-HASAN MEKARSARI BOGOR - Danapriatna, Nana; Kamilah, Ahya; Listyowati, Esi Asyani; Lutfiadi, Ridwan; Ismarani, Ismarani; Rahmanto, M. Ikhwan; Budiyono, Haris; Ardisela, Dawud (DEVOSI, 2025)
The increasing trend of a healthy lifestyle among urban communities has driven innovation in urban agriculture, one of which is aquaponics technology. Aquaponics is a sustainable farming system that integrates fish farming and plant cultivation within a single ecosystem, making it an effective solution for utilizing home yards. The Faculty of Agriculture at Universitas Islam 45 Bekasi, as a higher education institution, has a responsibility to implement the Tri Dharma of Higher Education, one of which is Community Service (PPM). This PPM activity aims to provide outreach and training on aquaponics to support the Diversified, Nutritious, Balanced, and Safe (B2SA) program at the Al-Hasan Mekarsari Foundation in Bogor. The program primarily involved female participants aged 21–30 years. The methods employed included education sessions, demonstrations, and hands-on practice in the installation and maintenance of aquaponic systems. The evaluation results indicated that participants comprehended the aquaponics concept and were capable of independently applying it at home. Furthermore, the program was perceived as beneficial in enhancing the availability of healthy food based on the B2SA principles within households. Through this initiative, the community is expected to adopt aquaponics technology as a practical solution for strengthening household food security and raising awareness of the importance of a healthy diet. Future sustainability of the program is anticipated to be expanded through further collaborations with various stakeholders to promote broader adoption of aquaponics in urban areas.